THE IMPACT OF THE POLITICAL CRISIS ON SMALL AND LARGE FIRMS IN THE REPUBLIC OF MACEDONIA - Majovski, Irina; Janevski, Zoran; Davitkovska, Elena (My University, 2018)
The recent political instability in the Republic of Macedonia has taken its toll on the business sector. During political instability, firms tend to postpone any major decision regarding future projects or investments as a result of changes in firms’ business perceptions and lack of predictability of future policies and trends. In this regard, a research was conducted among small, medium and large firms in the Republic of Macedonia in order to investigate the main consequences of the political crisis in the past few years on the business sector. The research findings reveal that the most severe implications of the political instability on businesses pertain to lack of long-term planning, decline in sales, increased difficulties related to collection of claims and implementation of ongoing contracts, and reluctance to conduct planned investments and recruitments. Results have also highlighted major differences between small and large firms in regard to perceived consequences of the political instability. Research on the effects of political instability on businesses is rather scarce in literature. Hence, the findings of this research are of particular importance for improving the knowledge about the potential implications of political instability on businesses and for identifying the main challenges that businesses face.
Keywords: political instability; business sector; small and large firms’ constraints